2005
DOI: 10.1111/j.1748-5827.2005.tb00321.x
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography as an aid in the diagnosis of chronic nasal disease in dogs

Abstract: CT greatly enhanced the ability to diagnose chronic nasal disease in dogs, providing detailed Information regarding the extent of the disease, accurate discrimination of neoplastic versus non-neoplastic diseases, and identification of areas of the nose to examine rhinoscopically and suspicious regions to target for biopsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
76
0
16

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(113 citation statements)
references
References 8 publications
8
76
0
16
Order By: Relevance
“…Nasal disease presents a diagnostic challenge due to non-specific clinical signs resulting from different nasal disorders (Tasker et al 1999, Lefebvre et al 2005. The radiological features of common nasal diseases have been described (Sullivan et al 1986, Sullivan et al 1987, Russo et al 2000.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nasal disease presents a diagnostic challenge due to non-specific clinical signs resulting from different nasal disorders (Tasker et al 1999, Lefebvre et al 2005. The radiological features of common nasal diseases have been described (Sullivan et al 1986, Sullivan et al 1987, Russo et al 2000.…”
Section: Introductionmentioning
confidence: 99%
“…The radiological features of common nasal diseases have been described (Sullivan et al 1986, Sullivan et al 1987, Russo et al 2000. Previous studies have shown radiography to have a poor specificity in differentiating inflammatory rhinitis from neoplasia or fungal rhinitis (Tasker et al 1999, Lefebvre et al 2005. However high accuracy and positive predictive value was found when differentiating rhinitis and nasal neoplasia based on the combination of radiographic signs (Russo et al 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The diagnosis of the type of orbital disease still depends on histopathologic examination after tissue sample collection (Park et al, 1992;Lefebre et al, 2005). Nasal CT greatly enhances the clinician's ability to diagnose and stage intranasal neoplasia.…”
Section: Discussionmentioning
confidence: 99%
“…Estas vantagens permitem que este seja um dos procedimentos mais indicados como método diagnóstico prévio nos casos suspeitos de afecção nasal, entretanto, não o torna exame de excelência diagnóstica, pois a interpretação radiográfica da cavidade nasal e das estruturas circundantes muitas vezes é prejudicada pela sobreposição de imagens, posicionamento inadequado do cão, além da variabilidade racial e estrutural do crânio destes animais (MYER, 1994;DOUST;SULLIVAN, 2004;DAVIDSON et al, 2004;POWDER;ROSE;CRAWFORD, 2006;DAVIDSON et al, 2004;LEFEBVRE;KUEHN;WORTINGER, 2005;ASHBAUGH, 2013;AULER et al, 2014) Já a tomografia computadorizada de cabeça (TCC), além de excelente ferramenta diagnóstica, vem também, há algum tempo, sendo indicada para avaliar o estadiamento do curso de afecções neoplásicas, auxiliando na escolha da modalidade terapêutica e sugerindo o prognóstico (LEFEBVRE; KUEHN;WORTINGER, 2005;ADAMS et al, 2009;AULER et al, 2015), principalmente em casos de câncer na região de cabeça e pescoço.…”
Section: Exames De Imagemunclassified